LEARNING STRATEGIES AND IMPLICATIONS FOR SECOND LANGUAGE TEACHING - Wang Dakun (Universitas Katolik Indonesia Atma Jaya, 2006)
This article reviews the relevant literature of language learning strategies by examining the background, the issues along with the definition, the characteristics, the categories and the functional framework. The intertwined relationships among person, task, context and strategies are illustrated with the tetrahedral model proposed by Gu (2003). The article also discusses the significance of language learning strategies for second language learning and the effectiveness of strategy instruction before presenting the pedagogical implications for second language teachers. The purpose of this article is to provide an overview of language learning strategy studies by summarizing the important aspects and to highlight the implications for integrating language learning strategy instruction into ESL classrooms so that the teachers can have a meaningful way to focus on their teaching efforts and the learners can become more efficient in their efforts to learn a second language as well.Keywords: learning strategies, second language teaching, strategy instruction